Balinese cultural representation from the perspective of the Balinese wordlist - Darmasetiyawan, I Made Sena (LingTera, 2025)
Based on the data gathered from the PARADISEC catalogue of the Balinese wordlist, as part of the OCSEAN project, 1,228 words were recorded and classified into several categories, such as the body, agriculture and vegetation, animals, the physical world, basic actions and technology, food and drink, spatial relations, kinship, motion, sense perception, quantity, emotions and values, cognition, time, speech and language, the house, warfare and hunting, possession, clothing and grooming, religion and belief, social and political relations, law, as well as miscellaneous function words. This study examines the Balinese wordlist from the OCSEAN data and explores the correlation between the number of words gathered and the speakers’ language recognition and comprehension within their community. Since the process of word recognition involves identifying both meaning and form (orthographic and phonological), these aspects originating from each speaker are generally influenced by their surrounding community. Through mapping the quantitative data, possible borrowings, and accuracy in the wordlist, several assumptions can be made. For example, the high number and accuracy of words related to agriculture (including its associated resources) may be attributed to the fact that many Balinese speakers come from farming communities. The implications of this study suggest that future research may benefit from combining pre-existing linguistic data with the psychological aspects of speakers and the cultural characteristics of their communities.